The study of the hypoglycaemic activity of GA, menthol and its GA: Mt (4: 1) supramolecular compounds in alloxan diabetes mellitus (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this article, we investigated the effect of GA and menthol supramolecular complex on blood glucose level and glycogen synthesis in liver of rats under conditions of alloxaninduced diabetes in the in vivo experiments we performed. According to the obtained results, menthol, GA and the GA:Mt (4:1) supramolecular compound derived from them can restore the functional impairment of liver mitochondria in alloxan-induced diabetes and inhibit the peroxidation of lipids in the membrane. In this case, the hypoglycemic activity and mitochondrial membrane stabilizing properties of the supramolecular compound GA:Mt (4:1) in the conditions of alloxan diabetes were shown to be stronger than menthol, GA and its compounds GA:Mt (2:1) and GA:Mt (9:1).